Two-Stage Linear Precoding for Generalized Frequency Division Multiplexing for Improved Performance - Sikri A.; Srinivas K.V. (My University, 2025)
Generalized Frequency Division Multiplexing (GFDM) is an attractive and recently proposed multicarrier modulation technique for the next generation wireless networks. However, GFDM suffers from self-interference problem due to the non-orthogonality of its subcarriers. In this paper, two novel schemes, each considering two-stage linear precoding, has been proposed that results in the improvement in the bit error rate (BER) performance of GFDM system with linear receivers. First schemes, considering linear MMSE receiver, results in achieving higher diversity gain in comparison to the GFDM system with one-stage precoding, while second scheme utilize two-stage precoding for the complete diagonalization of the modulation matrix. For second scheme, in addition to two-stage precoding, we consider signal space diversity (SSD) technique that results in achieving better performance. The validation of the improvement in the BER performance of GFDM system using proposed schemes has been shown through Monte Carlo simulations. © 2018 IEEE.